Pseudo real-time method for monitoring of the limiting anisotropy in membranes - Herman, P; Malinsky, J; Plasek, J; Vecer, J (Journal of fluorescence, 2004)
Data acquisition and analysis of the time-resolved fluorescence anisotropy is typically a time consuming process preventing usage of this experimental method for monitoring of time-dependent phenomena. We describe a method for pseudo real-time monitoring of the limiting fluorescence anisotropy r(infinity) allowing to track changes of the membrane order occurring on the time scale of minutes. Principle and performance of the method is demonstrated in the time domain with the time-correlated single photon counting detection. DMPC liposomes stained with 1,6-diphenyl-1,3,5-hexatriene (DPH) have been used to test influence of the diffusion membrane potential on the membrane order during the temperature-induced phase transition in DMPC membranes. It has been found that the transmembrane field of the order of -70 mV increases the phase transition temperature by about 1.5 degrees C-2 degrees C. It is proposed that the full advantage of the method can be utilized with a gated detection, which besides a faster data acquisition brings additional advantage of excitation light suppression. The method can be also used for imaging.
Keywords: Dimyristoylphosphatidylcholine; Membranes, Artificial; liposomy; Liposomes; membrány umělé; dimyristoylfosfatidylcholin